Engineering properties of Controlled Low-Strength Materials containing Treated Oil Sand Waste. (20th January 2018) - Mneina, A.; Soliman, A.M.; Ahmed, A.; El Naggar, M.H.
Highlights: Treated oil sand waste (TOSW) was successfully incorporated in CLSM mixtures. The effect of TOSW on the physical and mechanical properties was investigated. Environmental evaluation showed that TOSW can be safely used in CLSM. Abstract: Controlled Low-Strength Materials (CLSM) is a self compacted self-leveling cementitious material with compressive strength of 8.3 MPa or less. It is used as an alternative of soil backfill materials in geotechnical and infrastructure applications. This study investigates the effects of incorporating Treated Oil Sand Wastes (TOSW) as a partial replacement of sand or fly ash on fresh and hardened properties of CLSM. In addition, the environmental impact of the proposed new mixtures was evaluated. The results show that CLSM mixtures incorporating TOSW had satisfied the limits and requirements of ACI committee 229 for CLSM with no environmental hazards. The incorporation of TOSW has increased the flowability of all mixtures and consequently reduced the water demand to reach the required flowability which consequently increased the compressive strength of mixtures containing TOSW and flyash. Replacing flyash with TOSW on the other hand, reduced the strength of CLSM slightly, but the strength remains within CLSM acceptable range of strength. In addition, this produced a more re-excavatable mixture, adequate for applications that may require future re-excavation. This successful incorporation of TOSW in CLSM mixture will provide a safe recycling method for oil sand wastes while reducing the environmental footprint of both construction and oil sand industry.